FXR, MRP-1 and SLC7A5: New Targets for the Treatment of Hepatocellular Carcinoma - Zhang, Xi-yue; Luo, Ming; Qin, Shu; Fu, Wen-guang; Zhang, Meng-yu (Technology in cancer research & treatment, 2024)
Detect the expression of Farnesoid X Receptor(FXR), Multiple Drug Resistance Associated Protein-1(MRP-1) and Solute Carrier Family 7, Member 5 (SLC7A5) in hepatocellular carcinoma(HCC) of rat model, so as to provide new therapeutic targets for gene therapy of HCC. Sixty male Wistar rats were randomly divided into three groups. The rats in experimental group were given 0.2% diethylnitrosamine (DEN) by gavage with a dose of 10 mg/kg, 3 times a week, and it stopped at 12 weeks. The control group rats were given physiological saline by gavage, while the sham operation group did not receive anything by gavage. At 10 weeks, one rat in the experimental group was euthanized, and the changes of livers were recorded. The procedure was repeated at 12 weeks. After 12 weeks, HCC only occurred in the experimental group. After confirming the formation of the tumor through pathological examination, liver tissues and tumor tissues were taken from the three groups. FXR, MRP-1 and SLC7A5 expression in liver tissues and tumor tissues was detected. After 7 weeks the rats in experimental group ate less, and their weight was significantly reduced. Three months later, HCC was detected in 15 rats in the experimental group. The ratio of FXR/GAPDH mRNA, MRP-1/GAPDH mRNA, SLC7A5/GAPDH mRNA were significantly different among the three groups. Under the light microscope the FXR protein, MRP-1 protein, and SLC7A5 protein react with their respective antibodies, and they showed granular expression. Every pathological section included different numbers of positive cells in each group. FXR expression in HCC of rats was significantly lower than that in normal liver tissues, but MRP-1 and SLC7A5 expression in HCC were significantly higher than that in normal liver tissues, suggesting that drugs targeting FXR, MRP-1 and SLC7A5 may be new strategies for the treatment of HCC.